IMPLEMENTASI METODE PROFILE MATCHING DAN E-VOTING PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KETUA KARANG TARUNA BERBASIS WEBSITE - Abdul Rokhim; M. Wirshon Hadiyuddin (STMIK YADIKA BANGIL, 2022)
Abstract : In the development of information technology, especially in the electoral system, it is urgently needed to manage and present information, which includes the results of the election of youth leaders. Besides that, the solution to every problem is by utilizing the internet, online voting can increase voter participation and help restore public confidence in the electoral process. This method is safer and the results are accurate. Especially in the selection system for youth leaders in Babatan hamlet which has not been touched by computer technology. To facilitate the process of making information about the selection of youth leaders, a decision support system for Profile Matching and E-Voting methods was created to assist the process of selecting candidates for the selection of youth leaders of the Babatan Youth Association in Babatan Hamlet. By using this system, the admin can enter data on the candidate for chairman and voter data so that voters can log into the application and perform E-Voting on the candidate for chairman that was inputted earlier.